The Effect of Recruitment on Employee Performance at PT. Fokus Kualitas Utama - Faridz, Noor Laila Deviani; Nuruni Ika Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the effect of recruitment on employee performance at PT. Fokus Kualitas Utama. This research uses a qualitative approach with a case study type of research. The selection of research subjects was carried out using a purposive sampling technique, namely three informants who had different positions. Data collection methods were carried out using interviews, observation and documentation. In this research, data analysis was carried out through the stages of data reduction, data display, and verification with conclusion drawing. Test the validity of the data using the triangulation method. The results of this research show that recruitment has a very positive effect on the performance of PT. Fokus Kualitas Utama. Fokus Kualitas Utama, can be seen from the addition of employees made by the company that do not match the qualifications of the vacant positions so that employee performance is less than optimal.